Educate Kermit Roosevelt Through Sport Hunting and Train Him for Government Missions. Roosevelt Scientific Mission to English Equatorial Africa in 1909 - Chasles, Romain (Frontiers in Sports and Active Living, 2021)
The practice of sport hunting in colonized areas presents a set of knowledge and techniques indispensable to self-control and the domination of territories elsewhere by colonial empires, by their leaders and, more generally, by the political elites of the Northern states. During his scientific mission to English Equatorial Africa in 1909, Theodore Roosevelt responded to a double commission from the Smithsonian Institute and the American Museum in Washington. In this African mission, he brought and trained his youngest son Kermit, aged 20, in an initiatory journey. This article proposes to study this ritual of passage and the practice of sport hunting in the English colonial space as a revelation of the socio-racial hierarchies at work in the territories dominated by the English Empire.